2023
DOI: 10.3390/su151712750
|View full text |Cite
|
Sign up to set email alerts
|

Digital Influencers’ Attributes and Perceived Characterizations and Their Impact on Purchase Intentions

Manuel Joaquim de Sousa Pereira,
António Cardoso,
Ana Canavarro
et al.

Abstract: Research into the role of digital influencers in marketing strategies is a rapidly developing area that has attracted the interest of researchers and organizations. In recent years, organizations have become increasingly interested in using digital influencers to promote their brands and disseminate advertising messages with a high impact on their target audience. Digital influencers are beginning to be used as models for sustainable consumption behavior (for example in the fashion, food, and health sectors) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Social Attractiveness on Trustworthiness (H4a) has a P value of 0.020, a C.R value of 2.331 and an estimate value of 0.399, which means that social attractiveness on Trustworthiness has a positive significant relationship. This supports previous research in this study (Pereira et al, 2023) This study has a positive influence on the social attractiveness and trustworthiness of digital influencers. The results of this study also support previous research (Ert & Fleischer, 2020)This study has a significant positive effect on influencing perceptions of trust both directly and indirectly through perceived attractiveness, which is highly correlated with trust.…”
Section: Trustworthinesssupporting
confidence: 92%
See 1 more Smart Citation
“…Social Attractiveness on Trustworthiness (H4a) has a P value of 0.020, a C.R value of 2.331 and an estimate value of 0.399, which means that social attractiveness on Trustworthiness has a positive significant relationship. This supports previous research in this study (Pereira et al, 2023) This study has a positive influence on the social attractiveness and trustworthiness of digital influencers. The results of this study also support previous research (Ert & Fleischer, 2020)This study has a significant positive effect on influencing perceptions of trust both directly and indirectly through perceived attractiveness, which is highly correlated with trust.…”
Section: Trustworthinesssupporting
confidence: 92%
“…This research has a positive influence on the social attractiveness and trustworthiness of digital influencers(Pereira et al, 2023). Has a significant positive influence on influencing perceived trust both directly and indirectly through perceived attractiveness, which is highly correlated with trust(Ert & Fleischer, 2020).The same thing is found that in this research study attractiveness has a positive effect on trust in Arabic restaurants(Leung et al, 2022).…”
supporting
confidence: 75%
“…Public backlash or negative publicity can occur if an influencer's actions or statements conflict with brand values. Brands should mitigate this risk by having contingency plans in place, including a crisis communication strategy, to address any unforeseen issues swiftly and effectively [2,4,20].…”
Section: Mitigating Risks and Challengesmentioning
confidence: 99%
“…The evolution of influencer marketing can be traced to the rise of social media platforms, such as Instagram, YouTube, and TikTok, which provided a stage for individuals to build substantial online followings. Brands soon recognized the potential of collaborating with these influencers to authentically connect with their target demographics [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation